WEEDINESS OF A SHORT-TERM CROP ROTATION DEPENDING ON A FERTILIZER SYSTEM ON SOD-PODZOLIC SOILS - Gritsyuk, N. V.; Dovbysh, L. L.; Bakalova, A. V.; Puzniak, O. M. (Scientific Progress & Innovations, 2022)
In recent years there is a trend to create ecological, biological technologies of plants protection against pests, including weeds. Crop rotation is instrumental in them. The paper presents the results of a three-year field experiment, conducted during 2016–2018 on sod-podzolic loamy-sandy soils in a long-lasting stationary experiment. The paper shows some changes in weediness in terms of weed species and quantity. It also presents the yield indices of crops under a short-term crop rotation under different systems of mineral and organic fertilizing. It has been found out that species composition of weed synusia in crops under crop rotation did not show any significant regularity of its formation and did not depend on a fertilizer system. Quantitative changes in crop weediness depended on crop growing more than on applying mineral and organic fertilizers. When applying mineral fertilizer NPK 147 kg/hа + manure 10 t/ha the abundance and the accumulation of weed biomass in maize crop on the stage of full ripeness decreased by 20 items/м2 (2,5 g/m2). An insignificant decrease in the amount of weeds could be noticed under the application of green manure, straw and biological preparations. Under mineral system of fertilizing the amount of weeds on maize crops decreased by 10 %. On the stage of winter rye full ripeness the amount of weeds decreased by 6–12 items/м2 as compared with a variant without the application of fertilizers. The experiment has shown that under the organic fertilizer system (manure 10 t/ha +straw + green manure under maize and rye ) an increase in the amount of weed component by 20 %, as compared with a control variant, could be noticed. The expriment has also studied the yield indices of crops under a short-term crop rotation under different fertilizer systems when restoring fertilizer elements from soil by means of straw, green manure, biological preparations and organic fertilizers. It has been found out that during the research years the highest crop yield was registered under the application of organic and mineral systems of fertilizing, that has ensured the increase in winter rye yield by 1,7 t/ha, oats –by 1,5 t/ha, maize and annual grasses – by 1,1 t/ha.